5.62=Y+11.39

Simple and best practice solution for 5.62=Y+11.39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.62=Y+11.39 equation:


Simplifying
5.62 = Y + 11.39

Reorder the terms:
5.62 = 11.39 + Y

Solving
5.62 = 11.39 + Y

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-1Y' to each side of the equation.
5.62 + -1Y = 11.39 + Y + -1Y

Combine like terms: Y + -1Y = 0
5.62 + -1Y = 11.39 + 0
5.62 + -1Y = 11.39

Add '-5.62' to each side of the equation.
5.62 + -5.62 + -1Y = 11.39 + -5.62

Combine like terms: 5.62 + -5.62 = 0.00
0.00 + -1Y = 11.39 + -5.62
-1Y = 11.39 + -5.62

Combine like terms: 11.39 + -5.62 = 5.77
-1Y = 5.77

Divide each side by '-1'.
Y = -5.77

Simplifying
Y = -5.77

See similar equations:

| f(x)=x-5/x^2-10x-24 | | y=5x^2-10x-40 | | 7(3t-3)+4=-2 | | 7t^2-49t=126 | | 6(3x+4+2x-5)=54 | | 12-18Y-7Y+35=-8 | | 0=-6x^6-x^5-x^4-x^3+9x^2-9x+9 | | 4x^2+2x=25 | | (-4)-2y=8 | | y=-6x^6-x^5-x^4-x^3+9x^2-9x+9 | | -2(4+1)=22 | | 2/x=7-5/6x | | .75x-12=2x-2 | | 2/3b=3-5/6b | | F(x)=x^3+2x-4 | | x^5*x^2*x= | | (-6a^2)(3a^5)= | | 2x-5+12x=7-4x-12 | | 7x+1-8x=8(x+7) | | -24/-3 | | -13=5(v-2)-8v | | 0=-16t^2+96t+5 | | -4w=8-7w | | 3(x+2)=6x-15 | | 2+3(3x-4)=8-4(2x+1) | | 3(x+2)=6(x-15) | | 2z+9=57-6z | | 2-(-3+1)+4x+1=8 | | -12+3m=12 | | X^5-8x=0 | | 0.4(x+100)=0.45x-340 | | -15x+6+7x=3x+4 |

Equations solver categories